The Pen is the Sword: The Language of Battle in Veronica Franco’s Terze Rime - Ugolini, Paola (Quaderni d'Italianistica, 2023)
This article analyzes Veronica Franco’s use of the language of battle and swordsmanship in her Terze Rime, paying particular attention to the poems she wrote in response to a literary attack from an anonymous male writer (usually identified as Maffio Venier). In these texts, Franco describes the act of writing as a sword fight and represents herself as a skilled fencer. I consider Franco’s language of battle and her self-identification as a fighter in relation to the figure of the woman warrior popularized by Renaissance chivalric epics. Moreover, I explore the connections among Franco, her Terze Rime, and the Venetian cult of female figures—most significantly Saint Justina and the Virgin Mary—often represented as defenders of Venetian freedom. More broadly, this article investigates how Franco’s image of the pen as a weapon relates both to contemporary reflections on the position of women in society, as well as on the role and function of the writer in Renaissance Italy.